ANALISIS POLA KOMUNIKASI KELUARGA KELUARGA BESAR (EXTENDED FAMILY) TKI TERHADAP TUMBUH KEMBANG ANAK - Ekapti Wahjuni Djuwitaningsih (Jurnal Penelitian Komunikasi dan Opini Publik, 2018)
AbstractThe problems that occur when the housewife working as Female Labor (TKW) abroad, causing the relationship of communication patterns with the family is not running effectively, and no attention to children left behind, so the child does not get the full affection of his mother. To bridge the child in protection and compassion, the obligations and responsibilities of caring for, educating and raising children are left to the nuclear family and extended family. The applicable patterns of communication are the stimulus-response model, the abx model, the interactional model. The purpose of the study describes the communication patterns of TKW families. Determination of infroman with the technique of snow ball (snowball technique). Research location in Polorejo Village, District of Babadan, Regency of Ponorogo. The results of this study that the errors of communication patterns to children can lead to personal deviant children such as materialistic, child delinquency, promiscuity of children, and other deviant behavior. While the pattern of communication between father / husband to the wife abroad that is not intertwined in an intense and effective, it can cause berbabagi problems in family relationships such as divorce.Keywords: communication pattern, family, TKW